Automobile flame-retardant carbon fiber sheet and preparation method thereof
Patent Information
- Application Number
- CN202511697704.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-11-19
AI Technical Summary
Existing carbon fiber sheets are insufficient in terms of flame retardancy, wear resistance, and mechanical properties, making it difficult to meet the high safety and high durability requirements of automotive materials.
By introducing nitrogen and phosphorus-grafted polyacrylonitrile, modified carbon fiber, modified silica and metal composites, a synergistic flame retardant system is formed, which enhances the stability of the char layer and the interfacial bonding force, improves the flame retardant efficiency and wear resistance of the material, and increases the tensile strength and flexural modulus.
This achieves a balance between the high efficiency of flame retardancy, wear resistance, and mechanical properties of carbon fiber sheets, improving the overall performance of the material and meeting the load-bearing requirements of automotive structural components.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon fiber sheet technology, specifically to a flame-retardant carbon fiber sheet for automobiles and its preparation method. Background Technology
[0002] With the rapid development of the automotive industry towards lightweighting, energy conservation, and high performance, carbon fiber composite materials, with their advantages of low density, high specific strength, convenient molding, and strong adaptability, are widely used in key parts such as automotive body panels and structural support components. However, the comprehensive performance of traditional automotive carbon fiber sheets in terms of flame retardancy, wear resistance, and mechanical properties still needs further improvement, which seriously restricts their application in the field of high safety and high durability.
[0003] In terms of flame retardant performance, it often relies on adding a single flame retardant. Halogenated flame retardants release toxic gases when burned, which does not meet environmental protection regulations. Inorganic flame retardants need to be added in large quantities to be effective, but they can easily deteriorate the mechanical properties of the material. Moreover, conventional flame retardant systems lack synergistic effects between elements, making it difficult to form a dense and stable char layer during combustion. At high temperatures, heat and oxygen can easily penetrate the material, resulting in low flame retardant efficiency and failing to meet the high standards of automotive materials for flame spread suppression and smoke control. In terms of wear resistance, the surface fibers of traditional carbon fiber sheets are easily exposed, the bonding force between the fibers and the matrix is weak, the surface fibers are easy to fall off and fray during friction, resulting in severe wear and short life. Although some improved solutions are coated with wear-resistant layers, the adhesion between the coating layer and the matrix is poor, and it is easy to peel off after long-term use, thus failing to achieve durable wear resistance. In terms of mechanical properties, current carbon fiber sheets suffer from poor compatibility between the fiber and the matrix interface, uneven dispersion of fillers, and difficulty in effectively transferring stress. As a result, their tensile strength and flexural modulus cannot meet the load-bearing requirements of automotive structural components. Some modification schemes sacrifice mechanical properties to improve certain properties, making it difficult to achieve a balance between flame retardancy, wear resistance, and mechanical properties, and thus failing to meet the stringent requirements of automobiles for the comprehensive performance of materials. Summary of the Invention
[0004] The purpose of this invention is to provide a flame-retardant carbon fiber sheet for automobiles and its preparation method, in order to solve the technical problem that the flame-retardant performance, wear resistance, tensile strength and flexural modulus of carbon fiber sheets in the prior art need to be further improved.
[0005] The objective of this invention can be achieved through the following technical solution: a flame-retardant carbon fiber sheet for automobiles, comprising the following components by weight: 40-45 parts nitrogen-phosphorus grafted polyacrylonitrile, 25-30 parts modified carbon fiber, 4-8 parts modified silica, 6-12 parts metal composite, and 2-4 parts auxiliary additives.
[0006] Furthermore, the nitrogen-phosphorus grafted polyacrylonitrile is prepared by the following steps: A1. Add Na2CO3 aqueous solution dropwise to a reaction vessel containing hydroxylamine hydrochloride aqueous solution to adjust the pH of the solution to 5-6, then add polyacrylonitrile fiber to the reaction vessel, stir at 50-70℃ for 2-4 hours, and then perform post-treatment to obtain nitrogen-grafted polyacrylonitrile. A2. Nitrogen-grafted polyacrylonitrile is added to a reaction vessel containing phytic acid aqueous solution and stirred at 70-80℃ for 1-3 hours. After post-treatment, nitrogen-phosphorus-grafted polyacrylonitrile is obtained.
[0007] Reaction mechanism: Hydroxylamine hydrochloride dissociates into protonated hydroxylamine in aqueous solution. The added Na₂CO₃ passes through CO₃²⁻. 2- Hydrolysis produces OH - Neutralize excess H + The hydroxylamine group generated by the dissociation of hydroxylamine hydrochloride acts as a nucleophile and undergoes a nucleophilic addition reaction with the cyano group on the polyacrylonitrile fiber, converting the cyano group into a highly polar and reactive amine oxime group. Then, nitrogen-grafted polyacrylonitrile reacts with phytic acid. The hydrogen ions from the ionization of phytic acid protonate the oxime group. The phosphate group of phytic acid combines with the protonated oxime group through a coordinate bond, thereby grafting phosphorus onto it to obtain nitrogen-phosphorus-grafted polyacrylonitrile.
[0008] Further, in step A1, the ratio of the hydroxylamine hydrochloride aqueous solution to polyacrylonitrile fiber is 100-110 mL:1 g, the mass fraction of the hydroxylamine hydrochloride aqueous solution is 12%, and the mass fraction of the Na2CO3 aqueous solution is 10%. The post-treatment operation includes: filtering after the reaction, washing the product with deionized water 3-4 times, and then transferring it to a drying oven to dry to constant weight to obtain nitrogen-grafted polyacrylonitrile; in step A2, the ratio of the phytic acid aqueous solution to nitrogen-grafted polyacrylonitrile is 100-120 mL:1 g, the mass fraction of the phytic acid aqueous solution is 12%, and the post-treatment operation includes: filtering after the reaction, washing the product with deionized water 3-4 times, and then transferring it to a drying oven to dry to constant weight to obtain nitrogen-phosphorus-grafted polyacrylonitrile.
[0009] Furthermore, the modified carbon fiber is prepared by adding zinc nitrate to an aqueous solution of hexamethylenetetramine, stirring for 10-20 minutes, then adding carbon fiber, stirring at 80-90°C for 3-4 hours, and then performing post-treatment to obtain the modified carbon fiber.
[0010] Reaction mechanism: Hexamethylenetetramine hydrolyzes to produce ammonia and formaldehyde. Ammonia dissolves in water, making the solution weakly alkaline and slowly releasing OH-. ¯ Zn promotes the dissociation of zinc nitrate in solution. 2+ With OH ¯The zinc oxide ions are formed by combining and then gradually dehydrated to become zinc oxide, which is then directionally grown on the surface of the carbon fiber to achieve uniform coating of the carbon fiber with zinc oxide, and finally obtain modified carbon fiber coated with zinc oxide.
[0011] Furthermore, the ratio of zinc nitrate, hexamethylenetetramine aqueous solution, and carbon fiber is 3g:100mL:5-6g, the mass fraction of the hexamethylenetetramine aqueous solution is 2%, and the post-treatment operation includes: after the reaction is completed, filtering, washing the product with deionized water 3-4 times, and then transferring it to a vacuum drying oven and drying it at 90-100℃ for 6 hours to obtain modified carbon fiber.
[0012] Furthermore, the preparation method of the modified silica is as follows: nano-sized silica is placed in a reaction vessel containing anhydrous ethanol and deionized water, and ultrasonically dispersed at 20-30℃ for 20-30 min, followed by stirring for 10-20 min. Ammonia water is then added dropwise to adjust the pH of the solution to 8-9. The system is heated to 50-60℃, and vinyltriethoxysilane and 1H,1H,2H,2H-perfluorooctyltriethoxysilane are added. The reaction is carried out for 10-12 h, followed by post-treatment to obtain modified silica.
[0013] Reaction mechanism: First, nano-SiO2 is ultrasonically dispersed in an ethanol-water mixed solvent, exposing a large number of silanol groups on its surface. Then, ammonia is added to create a weakly alkaline environment. Vinyltriethoxysilane and 1H,1H,2H,2H-perfluorooctyltriethoxysilane undergo hydrolysis in the weakly alkaline environment to generate active silanol groups. Subsequently, the silanol groups generated by hydrolysis undergo a condensation reaction with the silanol groups on the SiO2 surface, removing water molecules and forming Si-O-Si covalent bonds. This allows vinyltriethoxysilane and 1H,1H,2H,2H-perfluorooctyltriethoxysilane to be grafted onto the SiO2 surface through chemical bonds, ultimately yielding a synergistically modified silicon-based material with both vinyl and perfluorooctyl groups on its surface.
[0014] Furthermore, the ratio of the nano-sized silica, anhydrous ethanol, deionized water, vinyltriethoxysilane, and 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 1-1.2 g:18 mL:2 mL:2 mL:2 mL; the post-treatment operation includes: after the reaction is completed, filtration is performed, the product is washed 2-3 times with deionized water, then washed 2-3 times with anhydrous ethanol, and then transferred to a drying oven to dry to constant weight to obtain modified silica.
[0015] Furthermore, the metal composite is prepared by the following steps: B1. The carbon fiber is impregnated in nitric acid solution at 70-80℃ for 2-3 hours, filtered, washed with deionized water 3-4 times, and then transferred to a vacuum drying oven and dried at 80-90℃ to constant weight to obtain pretreated carbon fiber. B2. Water-soluble phenolic resin, ZrOCl2·8H2O, Y(NO3)3·6H2O and deionized water are added to a reaction vessel and stirred at 70-80℃ for 30-60 min. Then the temperature is lowered to 40-50℃, and ammonia water is added dropwise to adjust the pH of the solution to 8-9. After stirring for 10-15 min, pretreated carbon fibers are added and impregnated at 100-110℃ for 8-10 h. After post-treatment, the metal composite is obtained.
[0016] Reaction mechanism: Carbon fibers undergo an oxidation reaction in nitric acid solution. The strong oxidizing property of nitric acid breaks the inert carbon bonds on the carbon fiber surface, generating active functional groups such as hydroxyl and carboxyl groups. Simultaneously, it removes surface impurities, providing sites for subsequent bonding with precursors. Water-soluble phenolic resin is dissolved and mixed with ZrOCl2·8H2O and Y(NO3)3·6H2O in deionized water to form a homogeneous solution. After cooling, ammonia is added dropwise to adjust the pH to weakly alkaline, allowing Zr... 2+ Y 3+ Hydrolysis occurs, generating precipitates of Zr(OH)4 and Y(OH)3. Simultaneously, phenolic resin is stably dispersed under weakly alkaline conditions, forming a mixed system containing Zr(OH)4, Y(OH)3, and phenolic resin. Finally, after adding pretreated carbon fibers, the oxygen-containing functional groups on their surface uniformly adhere Zr, Y precursors, and phenolic resin to the fiber surface through hydrogen bonding and coordination. After drying, the phenolic resin solidifies to form a precursor complex containing carbon fibers, hydroxides, and resin. Finally, under an argon atmosphere at 1600-1800℃, the phenolic resin carbonizes to generate carbon, Zr(OH)4 decomposes into ZrO2 and reacts with carbon to generate ZrC, and Y(OH)3 decomposes into Y2O3 and reacts with carbon to generate C2Y. Ultimately, a metal composite with carbon fibers as the base and ZrC and C2Y are formed.
[0017] Further, in step B1, the ratio of carbon fiber to nitric acid solution is 1g:20mL, and the mass fraction of nitric acid solution is 5%; in step B2, the ratio of water-soluble phenolic resin, ZrOCl2·8H2O, Y(NO3)3·6H2O, deionized water, and pretreated carbon fiber is 5-6g:3g:5g:80-100mL:12-15g. The post-treatment operation includes: after the reaction is completed, the reaction system is cooled to room temperature, filtered, the product is placed in a drying oven, dried at 90-100℃ to constant weight, and then reduced at 1600-1800℃ in an argon atmosphere for 2-3 hours to obtain the metal composite.
[0018] This invention also proposes a method for preparing flame-retardant carbon fiber sheets for automobiles, comprising the following: Nitrogen-phosphorus grafted polyacrylonitrile, modified carbon fiber, modified silica, metal composite and auxiliary additives are added to a high-speed mixer and mixed for 40-60 minutes at 150-180℃ and 300-500 r / min. Then the mixture is poured into a mold and held under pressure at 180-220℃ and 10-20 MPa for 20-40 minutes. Finally, the formed sheet is placed in a forced-air drying oven at 120-150℃ for annealing for 2-4 hours to obtain automotive flame-retardant carbon fiber sheets.
[0019] The present invention has the following beneficial effects: This invention introduces nitrogen and phosphorus elements through grafting polyacrylonitrile. Phosphorus promotes the formation of a dense char layer during combustion, while nitrogen dilutes combustible gases in the combustion zone and inhibits flame spread. The zinc oxide layer uniformly coated on the surface of modified carbon fibers catalyzes char layer formation and enhances char layer integrity. The metal composite, based on carbon fibers and incorporating high-melting-point ZrC and C2Y, forms a stable physical barrier at high temperatures, blocking heat and oxygen transfer. The silicon element and grafted functional groups on the surface of modified silica further enhance the stability and density of the char layer. Simultaneously, the surface vinyl groups can chemically bond with the grafted structure of nitrogen-phosphorus-grafted polyacrylonitrile and the active groups on the surface of modified carbon fibers, further strengthening the bond between the char layer and the matrix, ensuring that the char layer is not easily detached during combustion. In addition, perfluorooctyl groups can help reduce the release channels of combustible gases through the char layer, synergistically improving flame retardant efficiency with the nitrogen-phosphorus flame retardancy of nitrogen-phosphorus-grafted polyacrylonitrile, the catalytic effect of zinc oxide on the char layer of modified carbon fibers, and the high-temperature physical barrier of the metal composite.
[0020] The zinc oxide coating on the modified carbon fiber surface of this invention has high hardness and is tightly attached to the carbon fiber surface through chemical bonding, which can effectively resist wear during friction and reduce fiber shedding. The perfluorooctyl group grafted on the modified silica surface gives the material a certain degree of lubricity and reduces the coefficient of friction. At the same time, the chemical bonding between the vinyl group and the matrix ensures that it is not easy to detach from the matrix, avoiding the aggravation of wear due to particle shedding. The ZrC hard phase in the metal composite can enhance the scratch resistance of the material surface, and the grafting structure of nitrogen and phosphorus grafted polyacrylonitrile makes the matrix molecular chains more tightly bound, improves the matrix density, and reduces the generation of debris during wear. These substances work together to reduce the wear degree of the material during use and improve its wear resistance.
[0021] The modified carbon fiber of this invention enhances the interfacial bonding between the fiber and the matrix through the chemical bonding of zinc oxide to the carbon fiber surface, enabling stress to be effectively transferred between the fiber and the matrix. The carbon fiber matrix in the metal composite provides good toughness support, while the high-strength ZrC and C2Y phases endow the material with excellent rigidity. The two work together to improve the overall load-bearing capacity of the material. The silicon-oxygen bonds on the modified silica surface have excellent stability, and their chemical bonding with the matrix can disperse stress under stress, avoiding material damage caused by stress concentration. The grafting structure of nitrogen-phosphorus grafted polyacrylonitrile optimizes the arrangement and bonding state of the matrix molecular chains, improving the structural strength of the matrix itself. The stress transfer, rigidity complementarity, and structural reinforcement among the components work together to effectively improve the tensile strength and flexural modulus of automotive flame-retardant carbon fiber sheets. Detailed Implementation
[0022] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] In this application, the polyacrylonitrile fiber is selected from Taian Songze Composite Materials Co., Ltd., with a specification of 6mm and a diameter of 15μm; In this application, the carbon fiber is selected from Lingshou County Huashuo Mineral Products Processing Plant, with a mesh size of 325 mesh and a carbon content of ≥95%. In this application, the nano-sized silica is selected from Sichuan Hongjianxin Technology Co., Ltd., with CAS number 60676-86-0 and model number HJXY. In this application, the water-soluble phenolic resin is selected from Wuhan Jiyesheng Chemical Co., Ltd., with CAS number 9003-35-4, model number 99, and effective ingredient content of 99%.
[0024] Example 1 This embodiment provides a method for preparing flame-retardant carbon fiber sheets for automobiles, including the following steps: S1. Preparation of nitrogen-phosphorus grafted polyacrylonitrile Weigh 100 mL of 12 wt% hydroxylamine hydrochloride aqueous solution and add it to the reaction vessel. Then, add 10 wt% Na2CO3 aqueous solution dropwise to adjust the pH of the solution to 5. Next, add 1 g of polyacrylonitrile fiber to the reaction vessel and stir at 50 °C for 2 h. After the reaction is completed, filter the solution, wash the product three times with deionized water, and then transfer it to a drying oven to dry to constant weight to obtain nitrogen-grafted polyacrylonitrile. Weigh 100 mL of 12 wt% phytic acid aqueous solution and add it to the reaction vessel. Then add 1 g of nitrogen-grafted polyacrylonitrile and stir at 70 °C for 1 h. After the reaction is complete, filter the mixture, wash the product three times with deionized water, and then transfer it to a drying oven to dry to constant weight to obtain nitrogen-phosphorus-grafted polyacrylonitrile.
[0025] S2, Preparation of modified carbon fibers Weigh 3g of zinc nitrate and add it to 100mL of 2wt% hexamethylenetetramine aqueous solution. Stir for 10min, then add 5g of carbon fiber and stir at 80℃ for 3h. After the reaction is complete, filter the solution, wash the product three times with deionized water, and then transfer it to a vacuum drying oven and dry at 90℃ for 6h to obtain modified carbon fiber.
[0026] S3, Preparation of modified silica Weigh 1g of nano-sized silica and place it in a reaction vessel containing 18mL of anhydrous ethanol and 2mL of deionized water. First, ultrasonically disperse the silica at 20℃ for 20min, then stir for 10min. Add ammonia dropwise to adjust the pH of the solution to 8. Heat the system to 50℃, then add 2mL of vinyltriethoxysilane and 2mL of 1H,1H,2H,2H-perfluorooctyltriethoxysilane. React for 10h. After the reaction is complete, filter the product and wash it twice with deionized water and twice with anhydrous ethanol. Then, transfer the product to a drying oven and dry it to constant weight to obtain modified silica.
[0027] S4. Preparation of metal composites Weigh out 1g of carbon fiber and impregnate it in 20mL of 5wt% nitric acid solution. After impregnation at 70℃ for 2h, filter the solution, wash it three times with deionized water, and then transfer it to a vacuum drying oven and dry it at 80℃ to constant weight to obtain pretreated carbon fiber. Weigh out 5g of water-soluble phenolic resin, 3g of ZrOCl2·8H2O, 5g of Y(NO3)3·6H2O and 80mL of deionized water and add them to the reaction vessel. Stir at 70℃ for 30min, then cool to 40℃, add ammonia dropwise to adjust the pH of the solution to 8, stir for 10min, add 12g of pretreated carbon fiber, and impregnate at 100℃ for 8h. After the reaction is completed, let the reaction system cool to room temperature, filter, put the product into a drying oven, dry at 90℃ to constant weight, and then reduce at 1600℃ under an argon atmosphere for 2h to obtain the metal composite.
[0028] S5. Preparation of flame-retardant carbon fiber sheets for automobiles Weigh out the following by weight: 40 parts nitrogen-phosphorus grafted polyacrylonitrile, 25 parts modified carbon fiber, 4 parts modified silica, 6 parts metal composite and 2 parts auxiliary additives, add them to a high-speed mixer, mix at 150℃ and 300r / min for 40min, then pour into a mold, hold under pressure at 180℃ and 10MPa for 20min, and finally place the formed sheet in a 120℃ forced-air drying oven for annealing for 2h to obtain automotive flame-retardant carbon fiber sheet.
[0029] Example 2 This embodiment provides a method for preparing flame-retardant carbon fiber sheets for automobiles, including the following steps: S1. Preparation of nitrogen-phosphorus grafted polyacrylonitrile Weigh 105 mL of 12 wt% hydroxylamine hydrochloride aqueous solution and add it to the reaction vessel. Then, add 10 wt% Na2CO3 aqueous solution dropwise to adjust the pH of the solution to 5.5. Next, add 1 g of polyacrylonitrile fiber to the reaction vessel and stir at 60 °C for 3 h. After the reaction is completed, filter the solution, wash the product three times with deionized water, and then transfer it to a drying oven to dry to constant weight to obtain nitrogen-grafted polyacrylonitrile. Weigh 110 mL of 12 wt% phytic acid aqueous solution and add it to the reaction vessel. Then add 1 g of nitrogen-grafted polyacrylonitrile and stir at 75 °C for 2 h. After the reaction is complete, filter the mixture, wash the product three times with deionized water, and then transfer it to a drying oven to dry to constant weight to obtain nitrogen-phosphorus-grafted polyacrylonitrile.
[0030] S2, Preparation of modified carbon fibers Weigh out 3g of zinc nitrate and add it to 100mL of 2wt% hexamethylenetetramine aqueous solution. Stir for 15min, then add 5.5g of carbon fiber and stir at 85℃ for 3.5h. After the reaction is complete, filter the solution, wash the product three times with deionized water, and then transfer it to a vacuum drying oven. Dry at 95℃ for 6h to obtain modified carbon fiber.
[0031] S3, Preparation of modified silica Weigh 1.1g of nano-sized silica and place it in a reaction vessel containing 18mL of anhydrous ethanol and 2mL of deionized water. First, ultrasonically disperse the silica at 25℃ for 25min, then stir for 15min. Add ammonia dropwise to adjust the pH of the solution to 8.5. Heat the system to 55℃, then add 2mL of vinyltriethoxysilane and 2mL of 1H,1H,2H,2H-perfluorooctyltriethoxysilane. React for 11h. After the reaction is complete, filter the product. Wash the product twice with deionized water and twice with anhydrous ethanol. Then, transfer it to a drying oven and dry it to constant weight to obtain modified silica.
[0032] S4. Preparation of metal composites Weigh out 1g of carbon fiber and impregnate it in 20mL of 5wt% nitric acid solution. After impregnation at 75℃ for 2.5h, filter the solution, wash it three times with deionized water, and then transfer it to a vacuum drying oven and dry it at 85℃ to constant weight to obtain pretreated carbon fiber. Weigh out 5.5g of water-soluble phenolic resin, 3g of ZrOCl2·8H2O, 5g of Y(NO3)3·6H2O, and 90mL of deionized water and add them to a reaction vessel. Stir at 75℃ for 45min, then cool to 45℃, add ammonia dropwise to adjust the pH of the solution to 8.5, stir for 12min, add 13g of pretreated carbon fiber, and impregnate at 105℃ for 9h. After the reaction is complete, let the reaction system cool to room temperature, filter, put the product into a drying oven, dry at 95℃ to constant weight, and then reduce at 1700℃ under an argon atmosphere for 2.5h to obtain the metal composite.
[0033] S5. Preparation of flame-retardant carbon fiber sheets for automobiles Weigh out the following by weight: 42 parts nitrogen-phosphorus grafted polyacrylonitrile, 27 parts modified carbon fiber, 6 parts modified silica, 9 parts metal composite and 3 parts auxiliary additives, add them to a high-speed mixer, mix at 160℃ and 400r / min for 50min, then pour into a mold, hold under pressure at 200℃ and 15MPa for 30min, and finally place the formed sheet in a forced-air drying oven at 130℃ for annealing for 3h to obtain automotive flame-retardant carbon fiber sheet.
[0034] Example 3 This embodiment provides a method for preparing flame-retardant carbon fiber sheets for automobiles, including the following steps: S1. Preparation of nitrogen-phosphorus grafted polyacrylonitrile Weigh 110 mL of 12 wt% hydroxylamine hydrochloride aqueous solution and add it to the reaction vessel. Then, add 10 wt% Na2CO3 aqueous solution dropwise to adjust the pH of the solution to 6. Next, add 1 g of polyacrylonitrile fiber to the reaction vessel and stir at 70 °C for 4 h. After the reaction is completed, filter the solution, wash the product with deionized water 4 times, and then transfer it to a drying oven to dry to constant weight to obtain nitrogen-grafted polyacrylonitrile. Weigh 120 mL of 12 wt% phytic acid aqueous solution and add it to the reaction vessel. Then add 1 g of nitrogen-grafted polyacrylonitrile and stir at 80 °C for 3 h. After the reaction is complete, filter the mixture, wash the product with deionized water 4 times, and then transfer it to a drying oven to dry to constant weight to obtain nitrogen-phosphorus-grafted polyacrylonitrile.
[0035] S2, Preparation of modified carbon fibers Weigh 3g of zinc nitrate and add it to 100mL of 2wt% hexamethylenetetramine aqueous solution. Stir for 20min, then add 6g of carbon fiber and stir at 90℃ for 4h. After the reaction is complete, filter the solution, wash the product with deionized water 4 times, and then transfer it to a vacuum drying oven and dry at 100℃ for 6h to obtain modified carbon fiber.
[0036] S3, Preparation of modified silica Weigh 1.2g of nano-sized silica and place it in a reaction vessel containing 18mL of anhydrous ethanol and 2mL of deionized water. First, ultrasonically disperse the silica at 30℃ for 30min, then stir for 20min. Add ammonia dropwise to adjust the pH of the solution to 9. Heat the system to 60℃, then add 2mL of vinyltriethoxysilane and 2mL of 1H,1H,2H,2H-perfluorooctyltriethoxysilane. React for 12h. After the reaction is complete, filter the product and wash it three times with deionized water and three times with anhydrous ethanol. Then, transfer the product to a drying oven and dry it to constant weight to obtain modified silica.
[0037] S4. Preparation of metal composites Weigh out 1g of carbon fiber and impregnate it in 20mL of 5wt% nitric acid solution. After impregnation at 80℃ for 3h, filter the solution, wash it 4 times with deionized water, and then transfer it to a vacuum drying oven and dry it at 90℃ to constant weight to obtain pretreated carbon fiber. Weigh out 6g of water-soluble phenolic resin, 3g of ZrOCl2·8H2O, 5g of Y(NO3)3·6H2O and 100mL of deionized water and add them to a reaction vessel. Stir at 80℃ for 60min, then cool to 50℃, add ammonia dropwise to adjust the pH of the solution to 9, stir for 15min, add 15g of pretreated carbon fiber, and impregnate at 110℃ for 10h. After the reaction is complete, let the reaction system cool to room temperature, filter, put the product into a drying oven, dry at 100℃ to constant weight, and then reduce at 1800℃ under an argon atmosphere for 3h to obtain the metal composite.
[0038] S5. Preparation of flame-retardant carbon fiber sheets for automobiles Weigh out the following by weight: 45 parts nitrogen-phosphorus grafted polyacrylonitrile, 30 parts modified carbon fiber, 8 parts modified silica, 12 parts metal composite and 4 parts auxiliary additives, add them to a high-speed mixer, mix at 180℃ and 500r / min for 60min, then pour into a mold, hold under pressure at 220℃ and 20MPa for 40min, and finally place the formed sheet in a 150℃ forced-air drying oven for annealing for 4h to obtain automotive flame-retardant carbon fiber sheet.
[0039] Comparative Example 1 The difference between this comparative example and Example 3 is that step S1 is omitted, and the nitrogen-phosphorus grafted polyacrylonitrile in step S5 is replaced with the polyacrylonitrile in step S1.
[0040] Comparative Example 2 The difference between this comparative example and Example 3 is that step S2 is omitted, and the modified carbon fiber in step S5 is replaced with the carbon fiber in step S2.
[0041] Comparative Example 3 The difference between this comparative example and Example 3 is that step S3 is omitted, and the modified silica in step S5 is replaced with the nano silica in step S3.
[0042] Comparative Example 4 The difference between this comparative example and Example 3 is that step S4 is omitted and the metal composite is not added in step S5.
[0043] Performance testing: The oxygen index of the automotive flame-retardant carbon fiber sheets prepared in Examples 1-3 and Comparative Examples 1-4 was determined according to the standard FZ / T 50029-2015 "Test Method for Flame Retardant Properties of Synthetic Fiber Raw Material Chips - Oxygen Index Method" to represent their flame-retardant properties. The amount of fuzz on the automotive flame-retardant carbon fiber sheets prepared in Examples 1-3 and Comparative Examples 1-4 was determined according to the standard DL / T 2311-2021 "Technical Specification for Carbon Fiber for Composite Core Conductors" to represent the wear resistance of the carbon fiber sheets. The tensile strength and flexural modulus of the flame-retardant carbon fiber sheets prepared in Examples 1-3 and Comparative Examples 1-4 were determined according to the standard GB / T 39491-2020 "General Technical Requirements for Carbon Fiber Composite Covering Components for Automobiles". The specific test results are shown in Table 1 below: Table 1 - Performance Test Data of Samples Data Analysis: Comparative analysis of the data in Table 1 above shows that the automotive flame-retardant carbon fiber sheet prepared by this invention has an oxygen index of 36.1%, a fuzz weight of 0.085 mg / 50 m, a tensile strength of 315 MPa, and a flexural modulus of 27.8 GPa. Comparative Example 1 used ungrafted polyacrylonitrile instead of nitrogen and phosphorus grafted polyacrylonitrile, which lacked nitrogen to dilute combustible gases and phosphorus to promote the flame retardant effect of dense char layer. In addition, the matrix molecular chain was loosely bonded, resulting in a sharp drop in oxygen index to 28.5%, a fuzzing weight of 0.153 mg / 50m, a tensile strength of 280 MPa, a flexural modulus of 24.1 GPa, and impaired mechanical properties. Comparative Example 2, due to the replacement of modified carbon fiber with original carbon fiber, lacked the high hardness and wear resistance of the surface zinc oxide coating layer and the catalytic effect of the carbon layer, resulting in a fuzzing amount of 0.166 mg / 50 m, the worst wear resistance, an oxygen index that dropped to 29.9%, and weak interfacial bonding between the fiber and the matrix, with a tensile strength of 274 MPa and a flexural modulus of 25.2 GPa. Comparative Example 3, due to the replacement of modified silica with original nano silica, lacked the lubricating and stress-dispersing effects of perfluorooctyl and vinyl bonds, resulting in a fuzzing weight of 0.160 mg / 50 m, a tensile strength of 252 MPa, a flexural modulus of 22.5 GPa, and the worst mechanical properties. The oxygen index also dropped to 31.7%. Comparative Example 4, lacking the addition of metal composites, lacked the high-temperature physical barrier and rigid support formed by the high-melting-point ZrC and C2Y, resulting in an oxygen index of 31.4%, a fuzzing weight of 0.156 mg / 50 m, a tensile strength of 267 MPa, and a flexural modulus of 23.1 GPa. This demonstrates the crucial supporting role of the composite material in various properties.
[0044] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A flame-retardant carbon fiber sheet for automobiles, characterized in that, It includes the following components by weight: 40-45 parts nitrogen-phosphorus grafted polyacrylonitrile, 25-30 parts modified carbon fiber, 4-8 parts modified silica, 6-12 parts metal composite, and 2-4 parts auxiliary additives. A1. Add Na2CO3 aqueous solution dropwise to a reaction vessel containing hydroxylamine hydrochloride aqueous solution to adjust the pH of the solution to 5-6, then add polyacrylonitrile fiber to the reaction vessel, stir at 50-70℃ for 2-4 hours, and then perform post-treatment to obtain nitrogen-grafted polyacrylonitrile. A2. Add nitrogen-grafted polyacrylonitrile to a reaction vessel containing phytic acid aqueous solution, stir at 70-80℃ for 1-3 hours, and then perform post-treatment to obtain nitrogen-phosphorus-grafted polyacrylonitrile. Zinc nitrate was added to an aqueous solution of hexamethylenetetramine and stirred for 10-20 minutes. Then carbon fiber was added to the solution and stirred at 80-90°C for 3-4 hours. After post-treatment, modified carbon fiber was obtained. Nanoscale silica was placed in a reaction vessel containing anhydrous ethanol and deionized water. It was first ultrasonically dispersed at 20-30℃ for 20-30 min, then stirred for 10-20 min. Ammonia water was added dropwise to adjust the pH of the solution to 8-9. The system was then heated to 50-60℃, and vinyltriethoxysilane and 1H,1H,2H,2H-perfluorooctyltriethoxysilane were added. The reaction was carried out for 10-12 h, followed by post-treatment to obtain modified silica. B1. The carbon fiber is impregnated in nitric acid solution at 70-80℃ for 2-3 hours, filtered, washed with deionized water 3-4 times, and then transferred to a vacuum drying oven and dried at 80-90℃ to constant weight to obtain pretreated carbon fiber. B2. Water-soluble phenolic resin, ZrOCl2·8H2O, Y(NO3)3·6H2O and deionized water are added to a reaction vessel and stirred at 70-80℃ for 30-60 min. Then the temperature is lowered to 40-50℃, and ammonia water is added dropwise to adjust the pH of the solution to 8-9. After stirring for 10-15 min, pretreated carbon fibers are added and impregnated at 100-110℃ for 8-10 h. After post-treatment, the metal composite is obtained.
2. The flame-retardant carbon fiber sheet for automobiles according to claim 1, characterized in that, In step A1, the ratio of hydroxylamine hydrochloride aqueous solution to polyacrylonitrile fiber is 100-110 mL:1 g, the mass fraction of hydroxylamine hydrochloride aqueous solution is 12%, and the mass fraction of Na2CO3 aqueous solution is 10%. The post-treatment operation includes: filtering after the reaction, washing the product with deionized water 3-4 times, and then transferring it to a drying oven to dry to constant weight to obtain nitrogen-grafted polyacrylonitrile. In step A2, the ratio of phytic acid aqueous solution to nitrogen-grafted polyacrylonitrile is 100-120 mL:1 g, the mass fraction of phytic acid aqueous solution is 12%, and the post-treatment operation includes: filtering after the reaction, washing the product with deionized water 3-4 times, and then transferring it to a drying oven to dry to constant weight to obtain nitrogen-phosphorus-grafted polyacrylonitrile.
3. The flame-retardant carbon fiber sheet for automobiles according to claim 1, characterized in that, The ratio of zinc nitrate, hexamethylenetetramine aqueous solution, and carbon fiber is 3g:100mL:5-6g, and the mass fraction of the hexamethylenetetramine aqueous solution is 2%. The post-processing operation includes: after the reaction is completed, filtering, washing the product with deionized water 3-4 times, and then transferring it to a vacuum drying oven and drying it at 90-100℃ for 6 hours to obtain modified carbon fiber.
4. The flame-retardant carbon fiber sheet for automobiles according to claim 1, characterized in that, The ratio of nano-sized silica, anhydrous ethanol, deionized water, vinyltriethoxysilane, and 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 1-1.2 g:18 mL:2 mL:2 mL:2 mL. The post-treatment operation includes: after the reaction is completed, filtration is performed, the product is washed 2-3 times with deionized water, then washed 2-3 times with anhydrous ethanol, and then transferred to a drying oven to dry to constant weight to obtain modified silica.
5. The flame-retardant carbon fiber sheet for automobiles according to claim 1, characterized in that, In step B1, the ratio of carbon fiber to nitric acid solution is 1g:20mL, and the mass fraction of nitric acid solution is 5%. In step B2, the ratio of water-soluble phenolic resin, ZrOCl2·8H2O, Y(NO3)3·6H2O, deionized water, and pretreated carbon fiber is 5-6g:3g:5g:80-100mL:12-15g. The post-treatment operation includes: after the reaction is completed, the reaction system is cooled to room temperature, filtered, the product is placed in a drying oven, dried at 90-100℃ to constant weight, and then reduced at 1600-1800℃ under an argon atmosphere for 2-3 hours to obtain the metal composite.
6. A method for preparing a flame-retardant carbon fiber sheet for automobiles according to any one of claims 1-5, characterized in that, The process includes the following steps: Nitrogen-phosphorus grafted polyacrylonitrile, modified carbon fiber, modified silica, metal composite and auxiliary additives are added to a high-speed mixer and mixed for 40-60 minutes at 150-180℃ and 300-500 r / min. The mixture is then poured into a mold and held under pressure at 180-220℃ and 10-20 MPa for 20-40 minutes. Finally, the formed sheet is placed in a forced-air drying oven at 120-150℃ for annealing for 2-4 hours to obtain automotive flame-retardant carbon fiber sheets.
Citation Information
Patent Citations
C / C-ZrC composite material as well as preparation method and application thereof
CN106588044A
Preparation method of nitrogen / phosphorus-containing polyfunctional group axially modified fiber and application of nitrogen / phosphorus-containing polyfunctional group axially modified fiber in extraction of uranium from seawater
CN118002098A
